The controlled economy - Meade, J. E. (London : Allen and Unwin, 1971)
The book is divided into five parts: Part 1. Some Basic Concepts. Part 2. A Dynamic Model of the Economy. Part 3. The Theory of Indicative Forecasting. Part 4. Governmental Control Planning. Part 5. Residual Uncertainty and Economic Stabilization.
Includes index
rpm 01/11/2017
Loans
Keywords: Economic policy